Accountability mechanisms and the value of relationships: experiences of front-line managers at subnational level in Kenya and South Africa. Issue 4 (6th July 2018) - Nxumalo, Nonhlanhla; Gilson, Lucy; Goudge, Jane; Tsofa, Benjamin; Cleary, Susan; Barasa, Edwine; Molyneux, Sassy
Abstract : Resource constraints, value for money debates and concerns about provider behaviour have placed accountability 'front and centre stage' in health system improvement initiatives and policy prescriptions. There are a myriad of accountability relationships within health systems, all of which can be transformed by decentralisation of health system decision-making from national to subnational level. Many potential benefits of decentralisation depend critically on the accountability processes and practices of front-line health facility providers and managers, who play a central role in policy implementation at province, county, district and facility levels. However, few studies have examined these responsibilities and practices in detail, including their implications for service delivery. In this paper we contribute to filling this gap through presenting data drawn from broader ongoing research collaborations between researchers and health managers in Kenya and South Africa. These collaborations are aimed at understanding and strengthening day-to-day micropractices of health system governance, including accountability processes. We illuminate the multiple directions and forms of accountability operating at the subnational level across three sites. Through detailed illustrative examples we highlight some of the unintended consequences of bureaucratic forms of accountability, the importance of relational elements in enabling effective bureaucratic accountability, and the ways in which front-line managers can sometimes creatively draw upon one set of accountability requirements to challenge another set to meet their goals. Overall, we argue that interpersonal interactions are key to appropriate functioning of many accountability mechanisms, and that policies and interventions supportive of positive relationships should complement target-based and/or audit-style mechanisms to achieve their intended effects. Where this is done systematically and across key elements and actors of the health system, this offers potential to build everyday health system resilience.